THE STUDY OF THE PHYSICAL AND MECHANICAL PROPERTIES AND THERMAL CONDUCTIVITY COEFFICIENT OF ULTRA-LIGHT CONCRETE OBTAINED ON THE BASIS OF LOCAL VERMICULITE - Scientific Leader T.T. Shakirov,; Base Doctoral Student B.A. Tursunov,; A.Z. Odiljanov (Scholar Express Journal, 2022)
This article examines the issues of creating effective components of vermiculite slab, thermal insulation, sound-absorbing, refractory ultralightweight concrete with functional properties obtained on the basis of foamed vermiculite and studying their properties
Keywords: Foamed vermiculite; portland cement; liquid glass; thermal conductivity